A Destructive-Reconstructive Strategy to Engineer Low-Glycemic Dioscorea Alata Starch via Sequential Acid Hydrolysis and Retrogradation - Trinh, Khanh Son; Nguyen, Minh Hai; Tran, Huong Nguyen; Nguyen, Ngoc Bao; Nguyen, Vinh Tien (Journal of Technical Education Science, 2026)
A "destructive-reconstructive" strategy employing dual treatments of controlled acid hydrolysis and thermal retrogradation was investigated to engineer a novel, low-glycemic water yam starch. The starch was partially hydrolyzed with 0.5N HCl for varying durations (0, 4, 10, and 18 h) and subsequently retrograded by alternating cold (4°C, 18 h) and ambient (30°C, 6 h) temperatures for 48 hours. This modification induced significant changes in the starch’s physicochemical properties, including amylose content, molecular weight, and solubility, with FTIR analysis confirming the hydrolytic cleavage of starch chains into smaller fragments. A critical finding revealed that shorter hydrolysis times enhanced the formation of crystalline regions, thereby limiting subsequent acid and enzymatic degradation. Consequently, extending hydrolysis time systematically decreased the degree of relative crystallinity while concurrently increasing the in vivo glycemic index (iGI). The modified starches exhibited in vitro glycemic indices ranging from 35.25% to 49.23% and in vivo values from 51.07% to 64.67% relative to native starch. In vivo validation using a mouse model highlighted significant discrepancies from in vitro estimations, underscoring the necessity of physiological assessment for developing functional food ingredients. This dual modification demonstrates a promising approach for creating low-glycemic starches for individuals with diabetes and those on calorie-restricted diets.